Medium optimization for biobutanol production from palm kernel Cake (PKC) hydrolysate by clostridium saccharoperbutylacetonicum N1-4 - Muhd Arshad Amin,; Hafiza Shukor,; Noor Fazliani Shoparwe,; Muaz Mohd Zaini Makhtar,; Aidil Abdul Hamid,; Wichitpan Rongwong, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study aims to optimize the medium composition for biobutanol production using a Palm Kernel Cake (PKC) hydrolysate by Clostridium saccharoperbutylacetonicum N1-4. Various nutrient factors affecting biobutanol production were screened using the Plackett-Burman design. These factors included: NH4 NO3 , KH2 PO4 , K2 HPO4 , MgSO4 .7H2 O, MnSO4 .7H2 O, FeSO4 .7H2 O, yeast extract, cysteine, PABA, biotin, and thiamin. The results were analyzed by an analysis of variance (ANOVA), which showed that cysteine (P=0.008), NH4 NO3 (P=0.011) dan yeast extract (P=0.036) had significant effects on biobutanol production. The established model from the ANOVA analysis had a significant value of Pmodel>F = 0.0299 with an F-value of 32.82 which explains that the factors can explain in detail the variation in the data about the average and the interpretation is true with an R2 value of 0.993. The estimated maximum biobutanol production was 10.56 g/L, whereas the optimized medium produced 15.49 g/L of biobutanol. Process optimizations with optimum concentration of cysteine, NH4 NO3, and yeast extract have produced 21.33 g/L biobutanol which is a 37.7% improvement from the non-optimized medium. The findings show that PKC hydrolysate with the addition of optimal concentrations of the three types of medium namely, cysteine (0.15 g/L), NH4 NO3 (0.50 g/L), and yeast extract (1.5 g/L) during ABE fermentation, yielded a maximum biobutanol concentration of 21.33 g/L. Therefore, the results of this study provide good indications for promoting PKC hydrolysate as a new source of novel substrates with great potential in producing high biobutanol through ABE fermentation by C. saccharoperbutylacetonicum N1-4.